2017
DOI: 10.1021/acs.langmuir.7b01719
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Escin Molecules at the Air–Water Interface as Studied by Molecular Dynamics

Abstract: Escin belongs to a large class of natural biosurfactants, called saponins, that are present in more than 500 plant species. Saponins are applied in the pharmaceutical, cosmetics, and food and beverage industries due to their variously expressed bioactivity and surface activity. In particular, escin adsorption layers at the air-water interface exhibit an unusually high surface elastic modulus (>1100 mN/m) and a high surface viscosity (ca. 130 N·s/m). The molecular origin of these unusual surface rheological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 39 publications
(98 reference statements)
19
69
0
Order By: Relevance
“…Hence, either a fraction of the hydrophobic scaffold must be embedded in the aqueous subphase and/or the triterpenoid scaffold is strongly tilted with respect to the water-air interface. Both explanations are consistent with a recent simulation of β-aescin adsorption by molecular dynamics [42]. The inner layer, adjacent to the aqueous phase, was found to have a thickness of ≈1.4 nm.…”
Section: Structure Of the β-Aescin Monolayer At The Air-water Interfacesupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, either a fraction of the hydrophobic scaffold must be embedded in the aqueous subphase and/or the triterpenoid scaffold is strongly tilted with respect to the water-air interface. Both explanations are consistent with a recent simulation of β-aescin adsorption by molecular dynamics [42]. The inner layer, adjacent to the aqueous phase, was found to have a thickness of ≈1.4 nm.…”
Section: Structure Of the β-Aescin Monolayer At The Air-water Interfacesupporting
confidence: 91%
“…This will be discussed in more detail in Section 4. Also, the state of protonation was found to modify the inter-molecular interactions and thus the attractive and repulsive forces between β-aescin molecules [42,43].…”
Section: Micelle Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to a very specific arrangement of the aescin molecules inside the micelles. Molecular dynamics (MD) simulations by Tsibranska et al [52] for the self-assembly of aescin molecules at the water-air interface confirmed multiple attractive interactions between its hydrophobic and hydrophilic parts. Moreover, Penfold et al [43] proved this directed self-assembly experimentally by neutron reflectivity.…”
Section: Determination Of Cmc Aescinaf By Fluorescence Spectroscopymentioning
confidence: 98%
“…On the other hand, the area per molecule for Escin molecules is similar for air-water and Hexadecane-water interfaces, while the dilatational and shear elasticities are much lower for Hexadecane-water interface, which is probably related to the effect of hexadecane molecules on the orientation of the escin molecules in the adsorption layer. In our previous studies [60,61] we performed classical atomistic dynamics simulations of adsorbed escin molecules on the water surface. The results revealed that long-range attraction between the hydrophobic aglycones, combined with intermediate dipole-dipole attraction and short-range hydrogen bonds between the sugar residues in escin molecules control the viscoelastic properties of escin adsorption layers on air-water interface.…”
Section: Interfacial Rheological Properties Of Saponinsmentioning
confidence: 99%